Le million - Berr, Georges 1867-1942; Guillemaud, Marcel 1867-; Bernard, Armand; Parès, Philippe; Van Parys, Georges 1902-1971 (<<The>> Criterion Coll., 2000)
A musical comedy about a pair of young lovers who lose a lottery ticket worth a million francs and chase it frantically across Paris. Considered one of the very first musical films.
New digital transfer, with extensive image and sound restoration
Bildformat: 1.33:1 aspect ratio
Orig.: Frankreich 1931
Enth. a gallery of production photos ; a rare American television interview with René Clair
Keywords: Lottery winners - France - Paris - Drama; Lottery tickets -- France -- Paris -- Drama; Lottery winners -- France -- Paris -- Drama; Frankreich; France -- Drama; Paris (France) -- Drama; Feature films; Motion pictures, French; Musical films - France